Shadows of trauma: an umbrella review of the prevalence and risk factors of post-traumatic stress disorder in children and adolescents - Tadesse Tarik Tamir; Berhan Tekeba; Enyew Getaneh Mekonen; Deresse Abebe Gebrehana; Alebachew Ferede Zegeye (Child and Adolescent Psychiatry and Mental Health)
Abstract Introduction Post-Traumatic Stress Disorder (PTSD) is a significant mental health concern affecting children and adolescents, often resulting from exposure to traumatic events such as violence, natural disasters, or abuse. A substantial number of children and adolescents experience these traumatic events; however, the reported prevalence of PTSD in this population varies widely across systematic reviews and meta-analyses. This umbrella review aims to synthesize findings from multiple systematic reviews and meta-analyses to provide a comprehensive estimate of PTSD prevalence and identify key risk factors associated with the disorder. Methods A comprehensive literature search was conducted across several databases, including PubMed, Scopus, EMBASE, and others, using the COCOPOP framework. Systematic reviews and meta-analyses published between January 1, 2014, and December 1, 2024, were included. Data were extracted by two reviewers independently and analyzed using Stata 17 with a random-effects meta-analysis model. Results A total of twelve studies were included, with a combined sample size of 121,333 participants. The pooled prevalence estimate for PTSD among children and adolescents was found to be 25% (95% CI: 20-30%), with substantial heterogeneity (I² = 99.9%). Subgroup analyses indicated variations in prevalence based on publication year and the number of primary studies included in the systematic reviews. Key risk factors identified included older age, female gender, low social support, feelings of entrapment, and experiencing bereavement. Conclusions The prevalence of PTSD among children and adolescents exposed to trauma is notably high. Key contributing factors include older age, female gender, low social support, feelings of entrapment, and experiencing bereavement. Targeted interventions focusing on these risk factors, such as enhancing social support systems and providing early mental health interventions, are essential to improve outcomes for this vulnerable population. Further research is needed to refine these strategies and ensure they effectively meet the needs of children and adolescents affected by trauma.